Native gaming and gambling in Canada - Kiedrowski & Associates Inc. (Indian and Northern Affairs Canada, 2001)
Part 1 of this report reviews literature on the economic and social impact of Native gaming in Canada and the United States as well as material on the regulatory structure of tribal gaming in the United States and First Nations gambling in Canada. Part 2 of the report focuses on legal gaming schemes including Aboriginal gambling in the provinces and territories.